Linguistic Relationship and Dialect Variation of Banten Javanese and Sundanese in Indonesia - Dase Erwin Juansah; Akhmad Baihaqi; Odien Rosidin; Erwin Salpa Riansi (Universitas Syiah Kuala, 2025)
Banten people in Indonesia speak two different local languages: Banten Javanese and Banten Sundanese. In reality, it demonstrates that both languages share similarities in phonological and morphological patterns. The purpose of this study is to investigate the language kinship and dialect variations that occur within these local languages. This research employed a case study that involved eight native speakers of Banten Javanese from Serang, as well as eight native speakers of Banten Sundanese from Pandeglang and Lebak. In this study, non-participant observation was used to investigate the dialect variation used among the respondents. Then, semi-structured interviews and documentation were used to analyze the language kinship and separation time between Banten Javanese and Sundanese. The data were analyzed using Miles et al.s model in combination with Swadeshs lexicostatistical technique. The results revealed that (1) 51 pairs of identical words share both morphemic and phonemic similarities; (2) glottochronological estimates suggest that the separation of these local languages from the proto-language occurred between 1171 and 311 BC; and (3) regional dialects are the primary influence on the dialectal variation of these languages. Since these local languages are widely spoken in Banten, the findings reveal important linguistic relationships among local languages, emphasize the role of regional factors, and determine the value of glottochronology in tracing language development and variation